PENGARUH KUALITAS PELAYANAN DAN FASIITAS TERHADAP KEPUASAN PASIEN RAWAT INAP PADA RUMAH SAKIT PERTAMINA JAYA JAKARTA PUSAT - Abdul Qohar; Cornelia Dumarya Manik (Jurnal Manajemen & Pendidikan [JUMANDIK], 2025)
This study aims to determine the effect of Service Quality and Facilities on Inpatient Satisfaction at Pertamina Jaya Hospital, Central Jakarta. The method used is a descriptive quantitative method with an associative approach. The sampling technique applied is Probability Sampling, with sample selection using the Slovin formula. Data analysis employed regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. The results of this study indicate that Service Quality (X₁) and Facilities (X₂) have a significant effect on Patient Satisfaction (Y), with the regression equation obtained as:Y = 6.789 + 0.231X₁ + 0.592X₂. The coefficient of determination (R²) simultaneously between Service Quality (X₁) and Facilities (X₂) on Patient Satisfaction (Y) is 55.1%, while the remaining 44.9% is influenced by other factors not examined in this study. Partial hypothesis testing shows that the value for Service Quality (X₁) is t_calculated > t_table or (7.408 > 1.986), therefore H₀ is rejected and H₁ is accepted. This indicates a significant influence of Service Quality (X₁) on Patient Satisfaction (Y). For Facilities (X₂), the value obtained is t_calculated > t_table or (9.652 > 1.986), thus H₀ is rejected and H₂ is accepted, showing a significant effect of Facilities (X₂) on Patient Satisfaction (Y). Simultaneous hypothesis testing between Service Quality (X₁) and Facilities (X₂) yields f_calculated > f_table or (55.399 > 2.70), meaning H₀ is rejected and H₃ is accepted. This demonstrates a significant simultaneous influence of Service Quality (X₁) and Facilities (X₂) on Patient Satisfaction (Y)..